Brexit, Europe and othering. Issue 5 (23rd November 2020) - Van Der Zwet, Arno; Leith, Murray Stewart; Sim, Duncan; Boyle, Elizabeth
ABSTRACT: The UK has seen, within recent years, a noticeable increase in Euroscepticism, culminating in the vote to leave the European Union altogether. Although there were many reasons for the Brexit vote, the UK, in common with some other EU countries, had become increasingly concerned about rising levels of immigration, particularly from within the EU. This has led to an increase in a process of Othering those of a different background, nationality or religion, and ultimately the EU itself. This article seeks to explore aspects of othering of the EU in the UK, partly in the light of the Brexit vote. It focuses on the role of the media and political elites in this process. The article draws from secondary sources and sets out a research agenda based on seeking to understand the othering process of the EU, within the UK that requires further empirical research.